Health Extension Workers Involvement in the Utilization of Focused Antenatal Care Service in Rural Sidama Zone, Southern Ethiopia: A Cross-Sectional Study - Achamyelesh Gebretsadik; Million Teshome; Mekdes Mekonnen; Akalewold Alemayehu; Yusuf Haji (SAGE Publishing, 2019)
Background: Health extension workers (HEWs) are primarily been assigned in rural areas of Ethiopia to provide maternal and child health services. Few studies have been done to investigate HEWs' contributions towards maternal health services. This study describes HEWs involvement in the utilization of focused antenatal care (FANC). Methods: A population-based cross-sectional survey was conducted between January 21 and February 4, 2017. Mothers (2300) who gave birth in the last 6 months (0-6 months) in randomly selected 30 kebeles in the rural Sidama zone, participated in the study. A face-to-face interview was done using a structured questionnaire adapted from the Saving Newborn Lives Program. The main outcome variable was FANC utilization. Descriptive statistics and multivariate logistic regression analysis were used using SPSS statistical software. Results: The FANC was used by 525 (24.36%; 95% confidence interval [CI]: 22.5%-26.2%) women. Health extension workers accounted for 244 (46.47%; 95% CI: 43.5-47.7%) of mothers. The FANC utilization was less likely among those who were illiterate (adjusted odds ratio [AOR]: .32; 95% CI: .18-.57) and those who attended first cycle (AOR: .41; 95% CI: .23-.74), those who attended secondary cycle (AOR: .47; 95% CI: .27-.82), primipara (AOR: 0.53; 95% CI: .35-.83), and those who gave birth at home (AOR: .66; 95% CI: .51-.84). Mothers who had knowledge of pregnancy danger signs (AOR: 1.42; 95% CI: 1.2-1.7) and exposure to mass media (AOR: 1.35; 95% CI: 1.1-1.66) were more likely to utilize FANC. Conclusions: FANC utilization in this study was low compared to other studies. The HEWs had a major contribution to the services. However, it is low when compared to the plan set by the state ministry of health. The existing health extension program could be strengthened by increasing the number of HEWs. Empowering rural mothers through continuous education program to enhance the utilization of maternal health services.